2006
DOI: 10.1021/jp060018h
|View full text |Cite
|
Sign up to set email alerts
|

From Subtle to Substantial:  Role of Metal Ions on π−π Interactions

Abstract: Quantum chemistry calculations reveal that the subtle pi-pi interactions, usually in the range 2-4 kcal/mol, will become substantially significant, from 6 to 17 kcal/mol, in the presence of metal ion. The metal ions have higher affinity toward a pi-pi dimer compared to a single pi-moiety. Considering the widespread occurrence of cation-pi-pi motifs in chemistry and biology, as evident from the database analysis, we propose that the two key noncovalent forces, which govern the macromolecular structure, cation-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 15 publications
2
78
2
Order By: Relevance
“…Further, frequency calculations at B3LYP/6-31G(d) level of theory characterized all monomers as minima on the PES. From the literature, it is well known that the M05-2X functional is suitable for treating non-covalent interactions [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In our previous studies of phenylalanine, tyrosine and tryptophan monomers, we have also found the M05-2X functional to give satisfactory results [17][18][19].…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…Further, frequency calculations at B3LYP/6-31G(d) level of theory characterized all monomers as minima on the PES. From the literature, it is well known that the M05-2X functional is suitable for treating non-covalent interactions [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In our previous studies of phenylalanine, tyrosine and tryptophan monomers, we have also found the M05-2X functional to give satisfactory results [17][18][19].…”
Section: Methodsmentioning
confidence: 71%
“…Recent studies on the cooperativity of non-covalent interactions reveal that the manifestation of cooperativity is essential to understand various phenomena such as formation of supramolecular assemblies, catalysis and biological functions [1,[21][22][23][24]. His is an important model for the understanding of cation-π interactions due to its imidazole side chain [25][26][27][28][29][30][31][32][33][34][35][36]. Recently, the conformational analysis of neutral His [37] and its tautomers [38] has been reported in the gas phase using first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to assess the performance of computational methods by systematically increasing the size of the model system for the present case of stacking interactions. Hence, following the examination of the basis set and BSSE effect on the model benzene dimer, we ventured on exploring its effect on larger planar aromatic analog like naphthalene (2) and two of the prototypical buckybowls corannulene (3) and sumanene (4). The stacking interactions exhibited in the recently obtained crystal structure of sumanene triggered our interest to gauge the extent of interaction energy between these large p-bond complexes.…”
Section: Calculations On Naphthalene Corannulene and Sumanenementioning
confidence: 99%
“…Our recent work in the study of cation-π 16-22 interactions has improved our ability to understand this fundamental property of metal ion interactions. In the present study we have employed quantum mechanical calculations to obtain reliable estimates of the binding affinities of metal ions such as Li + , Na + and K + to the four model systems namely dehydro [12]annulene (1), dehydrobenzoannulene (2), dehydropyridoannulene (3) and dehydro [18]annulene (4), given in the scheme 1. Our objective in this study was to explore prospect of alkali metals as the sieving agents.…”
Section: Introductionmentioning
confidence: 99%
“…Our objective in this study was to explore prospect of alkali metals as the sieving agents. Since the interaction of the metal ion with dehydroannulene is highly dependent upon the nature of π-network and the cavity size, in the present study we have considered four different types of dehydroannulenes, among them three are dehydro [12] annulene and one is dehydro [18]annulene.…”
Section: Introductionmentioning
confidence: 99%